2016
DOI: 10.2106/jbjs.o.00201
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Whole-Blood Metal Ion Levels Among Four Types of Large-Head, Metal-on-Metal Total Hip Arthroplasty Implants

Abstract: Few studies of total hip arthroplasty (THA) implants with a large-diameter femoral head and metal-on-metal design have directly compared the progression of metal ion levels over time and the relationship to complications. As we previously reported, 144 patients received one of four types of large-diameter-head, metal-on-metal THA designs (Durom, Birmingham, ASR XL, or Magnum implants). Cobalt, chromium, and titanium ion levels were measured over five years. We compared ion levels and clinical results over time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 35 publications
1
19
1
Order By: Relevance
“…If we use the cutoffs for the levels of metal ions established by Van Der Straeten et al 28 (4.6 ppb for Cr and 4.0 ppb for Co), even in our short follow-up of two years, 12 patients with a HRA and 30 with a THA went from having safe levels to having unsafe levels. In contrast to other studies, [11][12][13][14][15][16][17] we show that the shedding of metal particles has not reached a state of equilibrium.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…If we use the cutoffs for the levels of metal ions established by Van Der Straeten et al 28 (4.6 ppb for Cr and 4.0 ppb for Co), even in our short follow-up of two years, 12 patients with a HRA and 30 with a THA went from having safe levels to having unsafe levels. In contrast to other studies, [11][12][13][14][15][16][17] we show that the shedding of metal particles has not reached a state of equilibrium.…”
Section: Discussioncontrasting
confidence: 99%
“…Currently, no such recommendations exist, and the data on mid-term changes in the levels of metal ions are sparse and inconsistent. 7,[9][10][11][12][13][14][15][16] Our aims were to determine whether measurements of metal ions in the blood change during extended follow-up, and whether specific cohorts of MoM patients merit closer follow-up than others. We found that for patients with both MoM HRAs and MoM THAs the levels of both Co and Cr ions increase between early and midterm follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, it does not follow a linear relationship, measuring metal ion levels in blood is an indirect way to estimate the extent of ion release from metallic implants. Since corrosion liberates metal ions, its magnitude may be estimated by quantifying the metal ion concentration in the blood of patients [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…10,44,45 Patients with ASR presented elevated blood and urinary levels of chrome (Cr) and cobalt (Co), while patients with other types of MoM implants usually have a slight elevation of such values. 46,47 However, for the latter implants, no symptoms or early failures have been addressed, as the experience reported in this series. Recently, patients with M2a acetabular MoM components (Biomet Orthopaedics, Warsaw, Indiana, United States) have shown high rates of pseudotumor at a mid-term follow-up, leading to revision in a percentage ranging from 4 to 8% and loosening in 31%; 13.8% of the studied hips had a definite adverse reaction to metal debris (ARMD), and 53.8% of the studied hips had a definite, probable, or possible ARMD.…”
Section: Discussionmentioning
confidence: 77%